ChemInform Abstract: I2‐Catalyzed Synthesis of Substituted Pyrroles from α‐Amino Carbonyl Compounds and Aldehydes. Issue 23 (10th June 2014) - Yan, Rulong; Kang, Xing; Zhou, Xiaoqiang; Li, Xiaoni; Liu, Xingxing; Xiang, Likui; Li, Yamin; Huang, Guosheng
Abstract A direct method for the synthesis of 1, 3, 4‐trisubstituted pyrroles is achieved easily from cyclization of α‐anilino carbonyl compounds and aldehydes catalyzed by iodine.